SARS-CoV-2 re-infection rate in Iranian COVID-19 cases within one-year follow-up. (December 2021) - Salehi-Vaziri, Mostafa; Pouriayevali, Mohammad Hassan; Fotouhi, Fatemeh; Jalali, Tahmineh; Banifazl, Mohammad; Farahmand, Behrokh; Sadat Larijani, Mona; Ahmadi, Zahra; Fereydouni, Zahra; Tavakoli, Mahsa; Karami, Afsaneh; Azad-Manjiri, Sanam; et al.
Abstract: Since the COVID-19 pandemic initiation, the possibility of re-infection has been unclearly present. Although herd immunity has a potential reliance through natural infection, human corona viruses has the ability to subvert immunity and re-infection happens for seasonal corona viruses. Currently, the frequency of SARS-CoV-2 re-infection incidence is not exactly defined. In this study we aimed at determination of SARS-CoV-2 re-infection rate in Iranian population. In a total of 5696 COVID-19 suspicious individuals, RT-PCR was applied to diagnose the infection. The confirmed patients were followed for 12 months and serology tests were applied to measure the specific antibodies. Among 1492 confirmed COVID-19 cases, five individuals experienced the subsequent infection. The re-infection/reactivation incidence rate was totally 0.33% after one year of follow-up. The interval ranged from 63 to 156 days. All the cases had viral mutations in the second episode of the infection. All of them were symptomatic cases with moderate severity. The estimated rate of SARS-CoV-2 in Persian population is therefore rare and natural infection seems to induce good protection against re-infection which clarifies that mass vaccination can hugely affect the society. Highlights: SARS-CoV-2 re-infection is a rare phenomenon. SARS-CoV-2 re-infections are mostly well tolerated and no more symptomatic than first infections. The evaluation of SARS-CoV-2 re-infection will help to find an appropriate solution to prevent re-infection.